Old Europe, new Europe and the US renegotiating transatlantic security in the post 9/11 era - Lansford, Tom; Tashev, Blagovest (Ashgate Pub., 2005)
This volume takes a specific look at the core security priorities of each European state and whether these interests are best served through closer security collaboration with the US or with emerging European structures such as the European Rapid Reaction Force.